The Relationship Between Alienated Labor and Private Property in Economic and Philosophical Manuscripts of 1844 - Fu, Shihu (Journal of Theory and Practice of Social Science, 2023)
Purpose: Because of the "circular argument", the relationship between alienated labor and private property has always been a theoretical difficulty, but in fact, Marx demonstrated the relationship between the two in detail in the Economic and Philosophical Manuscripts of 1844 from the two aspects of logical deduction and practical expression. In order to refute the so‐called "circular argument", it is necessary to clarify the relationship between the two. Research methodology: In the framework of Marxism theory combined with reality. And this is a qualitative study. Result: From the logical level, alienated labor is the essence, private property is only a phenomenon, that is, alienated labor is the cause of private property, otherwise the conclusion is not valid. From the perspective of reality, the two are interactive relations.